2020
DOI: 10.1109/lwc.2020.2969157
|View full text |Cite
|
Sign up to set email alerts
|

Denoising Higher-Order Moments for Blind Digital Modulation Identification in Multiple-Antenna Systems

Abstract: The paper proposes a new technique that substantially improves blind digital modulation identification (DMI) algorithms that are based on higher-order statistics (HOS). The proposed technique takes advantage of noise power estimation to make an offset on higher-order moments (HOM), thus getting an estimate of noise-free HOM. When tested for multipleantenna systems, the proposed method outperforms other DMI algorithms, in terms of identification accuracy, that are based only on cumulants or do not consider HOM … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…To show its scalability for real-world applications, the ISSA is applied for feature weighting in the context of blind digital modulation recognition for a multi-antenna system. The signals model and the identification system are the ones employed in [12]. The system model considers a frequency-flat block-fading multiple-input-multiple-output (MIMO) channel with m transmitting antennas and n receiving antennas.…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…To show its scalability for real-world applications, the ISSA is applied for feature weighting in the context of blind digital modulation recognition for a multi-antenna system. The signals model and the identification system are the ones employed in [12]. The system model considers a frequency-flat block-fading multiple-input-multiple-output (MIMO) channel with m transmitting antennas and n receiving antennas.…”
Section: Problem Formulationmentioning
confidence: 99%
“…The MD classifier identifies the modulation scheme by calculating the Euclidean distance of a feature vector with all the theoretical ones and then selecting the closest. In order to improve the performance of the identification system, authors in [12] introduced a feature-denoising approach. In our paper, for the same purpose, we will embed a feature weighting approach, i.e., we added weights to the initially extracted HOS so that the misclassification rate is minimized.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Under more extreme circumstances, only a few samples can be obtained and these methods will be not effective anymore. However, recent works have demonstrated that feature-based algorithms are still very efficient and improve classification performance with few training data [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Two general categories of algorithms can be used to solve AMC problems: likelihood-based (LB) [6][7][8][9][10][11][12] and feature-based (FB) [13][14][15][16][17][18][19][20][21][22]. LB algorithms are derived from three the likelihood ratio tests: average likelihood, generalized likelihood, and hybrid ratio test likelihood.…”
Section: Introductionmentioning
confidence: 99%